To the rescue! : Garrett Morgan underground - Kulling, Monica (Kulling, Monica. Great idea series., 2016)
Shares the inspirational story of African-American inventor Garrett Morgan, whose incredible safety hood became a forerunner to the gas masks that saved thousands of soldiers during World War I.